Studi Pemodelan Gedung Laboratorium Teknik Elektro Universitas Ibn Khaldun Bogor Berdasarkan Kapasitas Ruang dan Beban - Lutfi, Muhamad; Chayati, Nurul; Afrilia, Sintiya; Insan, Muhammad Khaerul; Wicaksono, Muhamad Hasan (Universitas Ibn Khaldun, 2025)
The Electrical Engineering Laboratory Building was built in 2017 with an existing building area of 120 m2, which is projected to serve 180 students. Based on the National Education Standards Agency (BSNP) in 2011 concerning the Draft Standards for Higher Education Facilities and Infrastructure for Postgraduate and Professional Programs states that the capacity of the lecture hall area is 2 m2 / student so that the basic building area is around 360 m2. The research objectives are to analyze the design and structure of the building regarding the capacity of the rooms and the loads that will act as well as to design and re-plan the building structure based on BSNP 2011 and SNI 1729-2020. The method used is primary data collection by direct measurement of the existing building, then analyzing the existing and planned structures with the DFBT / LRFD method using the ETABS V.21.0 application. The results of the analysis of space capacity, there are two rooms that are insufficient, which are classrooms and meeting rooms, so a new classroom is added on the second floor with an area of 40 m2 and an enlargement of the meeting room area to 50 m2. The results of the structural analysis of the existing building show failures in column sections C-48, C-51, C-50, C-43, C-38, C-33, C-28, C-66, C-26, C-20, C-11, C-3, C-45, C-41, C-35, C-30, C-31, and beam sections B-27, B-3. The results of the analysis of the planned structure using the WF 400.200.8.13 profile and the first floor beam structure elements using the WF 250.125.6.9 profile while the beam structure on the roof floor uses the WF 200.100.5.5.8 profile, the modeling analysis on the planned structure is declared safe against external forces on the building, and no structural elements have failed. The cost budget plan is calculated based on the 2021 Work Unit Price Analysis is IDR 1,547,000,000.00.